Revealing the effect of reaction parameters towards alkyl group distribution in in-situ transesterification of Chlorella vulgaris - Nguyen, T.T. (2019)
In-situ transesterification is a one-step reaction to produce biodiesel directly from biomass feedstock. However, the effect of reaction parameters in in-situ transesterification on alkyl group distribution was indefinite, especially when it involved microalgae biomass. In fact, the alkyl group distribution is an important factor to determine the quality of biodiesel. In the present study, the effect of catalyst, methanol and moisture content on fatty acid methyl ester (FAME) yield and composition produced from the in-situ transesterification of Chlorella vulgaris was investigated. The maximum FAME yield attained was 94.6 wt from the in-situ transesterification with H 2 SO 4 (at 80.8 mol/mol of H+ to esterifiable lipid). Although the moisture content is a detrimental factor in producing FAME from microalgae biomass, high FAME yield (>90 wt) could still be attained at the moisture content lesser than 15 wt. Besides, the catalyst type and concentration had shown a stronger effect on alkyl group distribution as compared with methanol and moisture content, in which the low polyunsaturated and high saturated FAME compositions were attained at low catalyst concentration (for KOH and H 2 SO 4 ) and high catalyst concentration (for KOH only), respectively. This could be attributed by the steric hindrance effect which was caused by the rotating flexibility of triglyceride alkyl groups during the in-situ transesterification and the rotating flexibility of FAME alkyl group during soap formation, respectively. Â© 2019 Elsevier Ltd